Perancangan Aplikasi Pengawasan Kegiatan Operasional Berbasis Web Di Direktorat Jenderal Kependudukan Dan Pencatatan Sipil Menggunakan Metode Waterfall - Dwi Nugraha, Gilang; Sakhi Faturrahman, Fawwaz; Rizan Fahrizi, Muhammad; Saprudin (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
Effective and efficient monitoring of operational activities is an important need to support the performance of an organization or company. However, the monitoring process carried out manually often causes various obstacles, such as late reports, inaccurate data, and difficulties in real-time monitoring. To overcome these problems, the software development method used in this study is the Waterfall method, which consists of the stages of needs analysis, system design, implementation, testing, and maintenance. The results of this design show that the application can help users in recording, reporting, and monitoring operational activities more quickly and accurately. With this system, it is hoped that the operational activity monitoring process will be more systematic and can increase the effectiveness of operational management.